Demokrasi di Ujung Tanduk: Peran Mahasiswa di Tengah Disinformasi dan Apatisme Politik - Jessica Dwi Anggraini; Anas Prasetyo; Rafly Ridho Pamungkas; Bryan Bakti Sambodo; Clara Beauty (CV. ITTC INDONESIA, 2026)
This study examines the strategic role of students in safeguarding and strengthening democracy in Indonesia amid the challenges of disinformation, identity politics, and the decline of substantive political participation. Students are positioned as agents of change who possess the intellectual and moral capacity to enhance public political literacy. This research employs a qualitative method using a literature review approach, drawing on books and scholarly articles relevant to democracy and student movements. The findings indicate that students have significant potential to increase public participation through digital activism and community-based engagement. However, this role is confronted by challenges such as political apathy, movement fragmentation, and disruptions in the digital era. Therefore, revitalizing student movements through the strengthening of digital literacy, organizational solidarity, and institutional collaboration is essential to ensuring the sustainability of democracy in Indonesia.